2021
DOI: 10.14742/ajet.6258
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness, efficiency, engagement: Mapping the impact of pre-lecture quizzes on educational exchange

Abstract: Our study addresses a systemic issue facing higher education – a lack of rigorous educational research alongside new technology-assisted ways of teaching and learning. The issue highlights the disciplinary disconnect as many academics do not research outside their discipline, yet are tasked with educational modernisation through trying out new educational technology. Addressing this issue, we present our conceptual framework, the course transaction space (CT-space), and use it to analyse the impact of an inter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 22 publications
1
7
0
Order By: Relevance
“…In the context of education, experiences with success contribute to developing self-efficacy, while failure impairs it (Usher & Pajares, 2009). The different levels of reported emotions related to an online quiz supports the suggestion from Evans et al (2021) that the frequent online quizzes may enable the development of self-efficacy.…”
Section: Habitualising Positive Affectsupporting
confidence: 55%
See 2 more Smart Citations
“…In the context of education, experiences with success contribute to developing self-efficacy, while failure impairs it (Usher & Pajares, 2009). The different levels of reported emotions related to an online quiz supports the suggestion from Evans et al (2021) that the frequent online quizzes may enable the development of self-efficacy.…”
Section: Habitualising Positive Affectsupporting
confidence: 55%
“…The impact of the online quizzes was analysed in a previous study by Evans et al (2021). They concluded that the intervention had optimised the impact of the distributed (spaced) practice on long-term memory retention.…”
Section: Methods Study Sitementioning
confidence: 99%
See 1 more Smart Citation
“…Another challenge discussed by Romero-Hall and Vicentini (2017, p. 153) was the lack of "adequate infrastructure (microphones, speakers, and adequate wireless internet) to help establish the interactions, communication, and sense of equality between all learners in the hybrid synchronous classroom." In addition, Evans, Kensington-Miller, and Novak (2021) added that one key challenge was the size of the course including the number of students enrolled in it per term. Thus, the aforementioned factors shall either contribute to the success and satisfaction of integrating hybrid learning or make it more challenging.…”
Section: Common Challenges Faced By Learnersmentioning
confidence: 99%
“…attendance and on-time assignment submissions). For instance, Evans et al (2021) demonstrated that when instructors in a prerequisite mathematics course incorporated frequent low stakes low difficulty pre-lecture online quizzes, observed benefits included: increased attendance, student engagement, and improved grades. The availability of the textbook could have a role in the intricate relations between attendance, On-time assignment submissions (OTAS), and final grades.…”
Section: Literature Reviewmentioning
confidence: 99%